Pengembangan Desain Alat Pirolisis Tipe Fast Pyrolysis dengan Reaktor Screw Bertingkat untuk Pengolahan Kulit Kopi (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
Pyrolysis is a biomass conversion method into fuel through heating at high temperatures under oxygen-limited conditions. The main factors influencing the pyrolysis process include temperature, residence time, pressure, particle size, reactor design, and the type of pyrolysis employed. This study aims to design an auger-type fast pyrolysis system based on previous research. The design and modeling of the fast pyrolysis equipment were carried out using Autodesk Inventor 2021 software. Based on the calculation and design results, a fast pyrolysis reactor with a multi-stage configuration and a capacity of 5.2 kg was developed. The system consists of a three-stage reactor made of Stainless Steel 304. The reactor is equipped with a screw conveyor for material transport, which is driven by an electric motor. Biomass heating inside the reactor is provided by a clamp heater with an electrical power requirement of 611 W, while biomass cooling is performed using a condenser with a cooling water capacity of 15.586 liters. Based on the structural simulation results, the maximum von Mises stress obtained was 35.4 MPa, the maximum displacement was 0.0528 mm, and the safety factor was 6.07 under loading conditions including an internal reactor pressure of 0.32 MPa, a torsional moment of 1,130 kg·mm, and an operating temperature of 700 °C. These values are within the allowable limits of the material, indicating that the designed reactor is structurally safe and feasible for use.